Knowledge and practices of breastfeeding mothers towards prevention of the emerging corona virus (COVID- 19) - Jamila Abuidhail; Faten Tamim; Rania Y. Abdelrahman; Eman Al-Shalabi (Elsevier, 2022)
Aim: To identify knowledge and practices of breastfeeding mothers towards prevention of the emerging corona virus (COVID- 19). Material and Methods: Cross-sectional design was used in this study. Data was collected via social media applications. Three hundred and seventy breastfeeding mothers completed the on-line survey. Questionnaire was assessing knowledge and practices of COVID- 19 related to breastfeeding. Results: The participating mothers have basic knowledge about COVID-19. Correct ''Preventive measures'' ranged from 84% to 99.7% but mothers have misconceptions regarding some modes of transmission, especially through blood & breast milk. In addition, they have a lack of understanding of how to deal with newborns of mothers infected or suspected to be infected with COVID-19 disease. Conclusion: Participants have basic knowledge about COVID-19 in general but they have improper preventive breastfeeding practices against the disease in particular. Nurses and midwives have the main role to increase awareness of breastfeeding mothers regarding preventive measures of COVID-19.